The Implementation of Project Based Learning integrated Ethno-STEM in Indonesia (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
This study is driven by the need to develop instructional approaches that foster 21st-century skills. As an archipelagic country with rich cultural diversity, Indonesia has significant potential to link cultural values with science education through the Ethno-STEM approach. The integration of Project-Based Learning (PjBL) with Ethno-STEM in Indonesia has demonstrated promising results. However, systematic investigations into research trends, local wisdom topics, and integration with other instructional approaches remain limited. Given the increasing interest in Ethno- STEM learning, this review aims to identify key trends and gaps in the integration of Project-Based Learning and Ethno-STEM in Indonesia over the past decade. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) framework was employed as a guideline for conducting the systematic literature review. Data were gathered using the Publish or Perish (PoP) application, drawing from the Google Scholar, Crossref, and OpenAlex databases. A rigorous selection process was applied, ultimately yielding 25 relevant articles for in-depth analysis. The findings reveal that the publication trend of PjBL-Ethno STEM in Indonesia has experienced significant growth since 2019, peaking in 2023. Development research (36%) and quantitative studies (32%) dominate the body of literature. Most of these studies were conducted on Java Island (76%), while no studies from Kalimantan and Papua were identified. The local wisdom topics explored in the literature include food, beverages, regional arts, traditional technologies, and native flora and fauna. Moreover, the integration of PjBL-Ethno STEM with inquiry-based learning, Ethno-STEAM, and virtual technology has emerged as a significant trend. Overall, PjBL-Ethno STEM stands out as an innovative instructional approach with great potential to cultivate essential 21st-century skills such as critical thinking, creative thinking, collaboration, and communication.